Blood flow restriction training (BFRT) -The benefits, consequences and the most effective protocol. - Richardson, L. J. F. (Journal of Australian Strength and Conditioning, 2020)
The purpose of this literature review was to investigate the benefits and potential consequences of blood flow restriction training (BFRT) and determine the most effective protocol for implementation. The Edith Cowan University (ECU) database was searched using the exact phrase and order of words "blood flow restriction training". After filtering and selecting articles that fitted the inclusion criteria, 29 peer-reviewed articles were selected for this literature review. BFRT in conjunction with various forms of exercise was found to improve strength, hypertrophy, aerobic capacity and muscle endurance, whilst reducing mechanical stress on the body. BFRT may induce minor cardiovascular system (CVS) stress, as well as slightly increase levels of discomfort and rate of perceived exertion (RPE) during exercise. Overall BFRT is an effective training modality, as it can be used to elicit positive training outcomes whilst reducing the mechanical stress on the body with minimal consequences if used correctly. The findings of this review suggest implementing a 4 set (1 x 30 rep, 3 x 15 rep) at low load (20 - 30% 1 RM) with 60% arterial occlusion pressure with single and multi-joint exercises to be the most effective method of administration for BFRT. The research indicates the most effective population to use this form of training is in a young, healthy or rehabilitation cohort of people.